Application Ability of Students in Integrated Computer-Aided Numerical Analysis Learning - Kosim Kosim (Journal of Mathematics Instruction, Social Research and Opinion, 2022)
The low ability of students to apply in numerical analysis courses is a problem in this research. Integrated learning is one solution to this problem. The aim is to determine the differences in student application abilities between integrated and conventional learning. One of the computer science colleges in the Cirebon area was sampled in this study. Two groups were formed, consisting of 1 integrated study group with a total of 36 students and one conventional study group with a total of 32 students. Both groups contracted numerical analysis courses. What carried out the type of quasi-experimental research and the static group comparison randomized control group only design became the design in this study. The result is that the average value of the application ability of students who study conventionally is 80.31, while the average application ability of students who study in an integrated manner is 84.58. The application ability of students who study integrated is higher than students who study conventionally, and the ability to apply of students who study integrated is more uniform than students who study conventionally. The results of the Mann-Whitney test found that the application ability of students who studied in an integrated manner was better than those who studied conventionally.